<span>1. If (-1, y) lies on the graph of y = 3^(x+1), then y = 3^(-1 + 1) = 3^0 = 1
2. If (x, 1/100) lies on the graph of y = 10^x, then 1/100 = 10^x
10^-2 = 10^x
x = -2
3. If (-1, y) lies on the graph of y = 2^2x, then y = 2^2(-1) = 2^(-2) = 1/4
4. The relationship between the graphs of y = 2^x and y = 2^-x is reflections over the y-axis.
5. If (3, y) lies on the graph of y = -(2x), then y = -2(3) = -6
6. All are not exponential
7. If (-2, y) lies on the graph of y = 4^x, then y = 4^(-2) = 1/4^2 = 1/16
8. If (-3, y) lies on the graph of y = 3^-x, then y = 3^-(-3) = 3^3 = 27
9. If (-3, y) lies on the graph of y = 3^x, then y = 3^(-3) = 1/3^3 = 1/27
10. If (-3, y) lies on the graph of y = (1/2)^x, then y = (1/2)^(-3) = 2^3 = 8</span>
Koolkid239
Angelica calculated the distance between the two points shown on the graph below.
Step 1: Use the point C(–4, –5) to make a right triangle with the 90 degree vertex at C.
Step 2: Determine the lengths of the legs: AC = 6 and BC = 10.
Step 3: Substitute the values into the Pythagorean theorem: mc010-2.jpg.
Step 4: Evaluate mc010-3.jpg
She states the length of AB is 8 units. Which best describes the accuracy of Angelica’s solution?
Angelica is correct.
Angelica made an error determining the location of the right angle. The right angle should be at (2, 5).
Angelica made an error counting the lengths of the legs of the right triangle. The lengths should be 7 and 11.
Angelica made an error substituting the values into the Pythagorean theorem. The equation should be mc010-4.jpg
Answer:
39
Step-by-step explanation:
The easy way to think about this is to think if it as 10%. You move the decimal one place to the left. so 130 becomes 13.0. if 10% of 130 is 13, what's 70%? multiply 13 by 7 And you get 91. that's not the answer. it's asking how many were NOT checked in for the flu, which is the other 30%. to get this, subtract the 91 (patients checked in for the flu) from 130 (total number of patients) and that gives you 39, the number of patients not checked in for the flu.
Answer:
(x4+1)(x2-2)
Step-by-step explanation:
x6-2x4+x2-2
separate them into two different expressions
(x6-2x4)+(x2-2)
factor out the common factor for each expression. For (x6-2x4), it would be x4, and for (x2-2), it would just be 1
x4(x2-2)+1(x2-2)
since there both expressions have the same factor, you can do a reverse of the distribution property and factor it like
(x4+1)(x2-2)
Answer:
12 loaves of bread
Step-by-step explanation:
If making one loaf of bread takes one cup of flour, using 12 cups you would make 12 loaves.